Gas permeability and selectivity of synthesized diethanol amine-polysulfone/polyvinylacetate blend membranes - Mushtaq, A. (Maxwell Science Publications, 2014)
The control of anthropogenic carbon dioxide release is one of the most challenging environmental problem faced by developing countries, as the interfering of atmospheric carbon dioxide level and climate revolutionize. An rising technology is the membrane gas separation, which is more dense, energy efficient and possibly more economical than past technologies, such as solvent absorption. Amine has a greater efficiency for removal of carbon dioxide. The blending technique not only provides improved chemical and thermal stability but is also efficient enough to improve the perm-selective properties with economical viability. In this study, research will be carried out to study the gas permeability behavior of glassy Polysulfone and Polyvinyl acetate rubbery polymeric blend membranes with diethanol amine. Polymeric amine blend membranes with different blending ratios were prepared in dimethyl acetamide solvent, flat sheet membrane were developed with enhance properties. We were studied PSU/PVAc blend with DEA amine using a gas permeability application for CO2 and CH4 at different feed pressures. Â© Maxwell Scientific Organization, 2014.